From Caá-ehé to a Commercial Sweetener – the Diterpenoid Glycosides of Stevia rebaudiana. (December 2016) - Hanson, James R.
The isolation, structure elucidation, chemistry, biosynthesis and biological activity of the sweet steviol glycosides from Stevia rebaudiana, are reviewed.